2010
DOI: 10.3858/bmbrep.2010.43.5.362
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the solution structure of the human antibiotic peptide dermcidin and its interaction with phospholipid vesicles

Abstract: Dermcidin is a human antibiotic peptide that is secreted by the sweat glands and has no homology to other known antimicrobial peptides. As an initial step toward understanding dermcidin's mode of action at bacterial membranes, we used homonuclear and heteronuclear NMR to determine the conformation of the peptide in 50% trifluoroethanol solution. We found that dermcidin adopts a flexible amphipathic α-helical structure with a helix-hinge-helix motif, which is a common molecular fold among antimicrobial peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…We presume that the cationic N-terminal part is mainly responsible for the binding of DCD-1L to the bacterial surface and to the negatively charged bacterial phospholipids. This view was recently proposed by Jung et al who used liquid state NMR to solve the structure of DCD-1L in 50% TFE and to characterize its interaction with phospholipid vesicles (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presume that the cationic N-terminal part is mainly responsible for the binding of DCD-1L to the bacterial surface and to the negatively charged bacterial phospholipids. This view was recently proposed by Jung et al who used liquid state NMR to solve the structure of DCD-1L in 50% TFE and to characterize its interaction with phospholipid vesicles (40).…”
Section: Discussionmentioning
confidence: 99%
“…5D suggests that the cationic N-terminal region of DCD-1L might form a toroidal pore across the lipid bilayer, while the amphiphilic C terminus remains floating on the membrane surface. The secondary structure prediction of DCD-1L as well as the experimental NMR structure in 50% TFE (40) had shown an intrinsically flexible amphiphilic structure with three distinct ␣-helical regions, which would readily allow a sharp turn in the middle of the sequence. By forming either an intramolecular helical hairpin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides possess a potent and widespectrum antimicrobial activity against S. aureus, E. coli, Enterococcus faecalis, Listeria monocytogenes, Salmonellae, Pseudomonas and Candida albicans (Hata & Gallo, 2008;Pathak et al, 2009). By means of nuclear magnetic resonance it has been established that DCD-1 has an -helical structure with a helix-hinge-helix motif, which is a common molecular fold among antimicrobial peptides (Jung et al, 2010). It seems that the affinity with which DCD-1 binds to bacterial-mimetic membranes is primarily dependent on its amphipathic -helical structure and its length (>30 residues), whereas its negative net charge and acidic isoelectric point have little effect on binding.…”
Section: Dermcidinmentioning
confidence: 99%
“…Using immune electron microscopy, it has been shown that DCD-1 antimicrobial activity originates with its binding to the bacterial membrane, and that the molecule effectively kills S. epidermidis. DCD-1L shows stronger antimicrobial activity than the parent peptide, and it is highly effective against drugresistant S. aureus, as well as other Gram-positive and Gram-negative bacterial strains (Jung et al, 2010). The mechanisms by which DCD-derived peptides kill bacteria are still unclear.…”
Section: Dermcidinmentioning
confidence: 99%
“…Antimicrobial peptides are produced in a variety of plants and animals for host defense against microbial infection. A number of different antimicrobial peptides (>880) has been identified or predicted based on nucleic acid sequences (1)(2)(3). Antimicrobial peptides can be classified by composition and structure of amino acids into subgroups (1,4).…”
Section: Introductionmentioning
confidence: 99%